Interactive Multimedia Based on the PjBL Model with Tri Kona Concept Orientation to Enhance Science Literacy of Fourth-Grade Students - Ida Ayu Oka Purnami; Ni Luh Putu Elly Ardani; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Jurnal Media dan Teknologi Pendidikan, 2025)
The low scientific literacy of elementary school students is a challenge in meaningful and contextual science learning. Learning that is still conventional and does not actively involve students also worsens the understanding of scientific concepts. This study aims to prove the effectiveness of interactive multimedia based on the Project Based Learning (PjBL) model with the Tri Kona concept orientation to improve the scientific literacy of fourth grade students. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study included 26 fourth grade IVA students as the experimental group and 25 fourth grade IVB students as the control group. This development research uses two types of data, namely qualitative and quantitative data. The methods and instruments for data collection in this study used questionnaires and multiple-choice tests. The results of the study showed that the multimedia developed was very feasible to use, interesting, and effective in improving students' scientific literacy. The implications of this study indicate that the development of media based on PjBL and local cultural values can be an innovative strategy in science learning in elementary schools.